THERMODYNAMICS OF CONGO RED DYE ADSORPTION PROCESSES ON MINERAL AND CARBON ADSORBENTS - Mehmonxonov, Mansurxon; Ergashev, Oybek; Abdikamalova, Aziza; Bakhronov, Khayot; Askarova, Dilzoda; Xudoyberdiyev, N; Xolikov, Kamoliddin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This paper investigates the thermodynamic aspects of the adsorption processes of Congo red dye on four different types of adsorbents: steam-activated brown coal, enriched bentonite from Navbahor deposit, carbon based on waste polyethylene terephthalate bottles and Fe-intercalated bentonite. The study focuses on the analysis of enthalpy and entropy changes, which allow to estimate the energy efficiency and spontaneity of the adsorption processes. The results show that the adsorption of the dye is endothermic and is accompanied by a decrease in entropy, which indicates a significant degree of ordering during adsorption. The role of temperature in the efficiency of adsorption processes is emphasized and recommendations for the use of these adsorbents for wastewater treatment are proposed.